EFFECTS OF REPLACEMENT FERULA COMMUNIS (Giant fennel) IN DIET ON PRODUCTIVE PERFORMANCE AND SOME PHYSIOLOGICAL PARAMETER IN JAPANESE QUAIL. - Tayeb, Ihsan Tawfeeq (IRAQI JOURNAL OF AGRICULTURAL SCIENCES, 2022)
This study was conducted at the animal production department, College of Agriculture Engineering Sciences , University of Duhok, in order to investigate the effect of ration replacement with ferula on productive performance and some physiological parameters of quail. Three hundred sixty day old quail birds were divided into four groups with three replicates , group (30 birds replicate, the groups were treated from the age of 7days till the age of 42days as follows: T1(control): Reread on standard ration, T2: Reread on standard ration replaced with 10% ferula, T3: Reread on standard ration replaced with 15% ferula, T4: Reread on standard ration replaced with 20% ferula. The results revealed significant increases in live body weight (LBW) and body weight gain (BWG) of treatment as compared with control in all weeks. A significant increases in carcass weight, dressing percentage of ferula treatments as compared with control. Significant decreases mortality percentage of ferula treatments as compared with control group. Significant decreases in albumin and serum glucose in ferula as compared with control groups.